Evaluation of Fowler–Stephens orchiopexy for high-level intra-abdominal cryptorchidism: A systematic review and meta-analysis. (December 2018) - Yu, Chengjun; Long, Chunlan; Wei, Yi; Tang, Xiangliang; Liu, Bin; Shen, Lianju; Dong, Xueyi; Lin, Tao; He, Dawei; Wu, Shengde; Wei, Guanghui
Abstract: Background and objective: There has been no consensus regarding the best surgical strategy for patients with cryptorchidism involving high-level intra-abdominal testes. This systematic review and meta-analysis compared the outcomes of Fowler–Stephens orchiopexy (FSO) conducted as 1-stage or 2-stage, open or laparoscopic. Methods: The databases PubMed, Cochrane Library, Web of Science Database, Russian Science Citation Index, SciELO Citation Index, China National Knowledge Infrastructure, WanFang Data, and China Biology Medical disc were systematically searched for relevant articles. Results: Sixty studies involving 1991 operated testes were included in the final analysis. The overall success rates for 1- and 2-stage FSOs were 85% and 87%, respectively; overall atrophy rates for both were 10%. The success rates of 1-stage FSOs, open and laparoscopic, were 83% and 87%; with atrophy rates of 12% and 8%. The corresponding success rates of 2-stage FSOs were 81% and 89%; with atrophy rates of 17% and 8%. The odds ratios indicated that 2-stage FSO was significantly superior to 1-stage, and laparoscopic superior to open. Evaluating laparoscopic FSO over time, the success rates prior to year 2000, 2000 through 2010, and after 2010 were 85%, 89%, and 88%, and atrophy rates were 15%, 9%, and 6%, with no heterogeneity in the reports, and the funnel plot showed no publication bias. Conclusion: Each surgical technique for correcting high-level intra-abdominal testes (IATs) had an acceptable success rate, from 81% to 89%. However, in terms of highest success rate and lowest atrophy rate, 2-stage laparoscopic FSO is the first choice for treating high intra-abdominal cryptorchidism. Highlights: The overall 2-stage Fowler–Stephens orchiopexy (FSO) achieved significantly better success rates compared with 1-stage FSO. The 2-stage laparoscopic FSO had a significantly better success rate compared with 1-stage laparoscopic FSO. Laparoscopic FSO was significantly superior to open FSO, with regard to success rate. The available data was too limited to make a comparison between 1-stage and 2-stage open FSO. The atrophy rates of laparoscopic FSO for high-level intra-abdominal cryptorchidism have decreased with year goes by.